Right ventricular 2D speckle-tracking echocardiography in children with osteosarcoma under chemotherapy - Khairat, Ibtsam (Egypt Heart J, 2019)
BACKGROUND: Cardiotoxicity from anthracyclin chemotherapy is a leading cause of death in patients with cancer. Therefore, left ventricular (LV) function is routinely assessed during protocol to detect cardiotoxicity; however, animal studies suggest that right ventricular (RV) function may be also impaired. So, our objective was to investigate the incidence of RV dysfunction in children with osteosarcoma receiving anthracyclines and to highlight the role of 2D STE in early detection of RV dysfunction. RESULTS: RV function was affected by anthacyclines through direct cardiotoxic effect on RV myocardium without simultaneous derangement of LV function. Furthermore, there is a direct proportion between the incidence of RV dysfunction and the cumulative dose of anthracyclines. At the first echo follow-up at 10th week, 7 patients had impaired RV GLS in comparison to baseline study. At 20th week, the number of patients with impaired RV strain increased to 10. At 29th week, it reaches 12 patients. This effect was early detected by RV 2DSTE before adversely affecting TAPSE and FAC. The incidence of RV dysfunction from anthracyclines was around 12%, and the recovery rate was around 8% in 3 months after completion of chemotherapy. CONCLUSION: RV 2DSTE is the best modality to detect early affection of RV function in comparison with other modalities. RV function decreases early even before derangement of LV function. Accordingly, it should be assessed separately in all patients who received anthracyclines even without evident LV affection.